On-call work: To sleep or not to sleep? It depends. (2nd July 2016) - Ferguson, Sally A.; Paterson, Jessica L.; Hall, Sarah J.; Jay, Sarah M.; Aisbett, Brad
ABSTRACT: On-call working time arrangements are increasingly common, involve work only in the event of an unpredictable incident and exist primarily outside of standard hours. Like other non-standard working time arrangements, on-call work disrupts sleep and can therefore have negative effects on health, safety and performance. Unlike other non-standard working time arrangements, on-call work often allows sleep opportunities between calls. Any sleep obtained during on-call periods will be beneficial for waking performance. However, there is evidence that sleep while on call may be of substantially reduced restorative value because of the expectation of receiving the call and apprehension about missing the call. In turn, waking from sleep to respond to a call may be associated with temporary increases in performance impairment. This is dependent on characteristics of both the preceding sleep, the tasks required upon waking and the availability and utility of any countermeasures to support the transition from sleep to wake. In this paper, we critically evaluate the evidence both for and against sleeping during on-call periods and conclude that some sleep, even if it is of reduced quality and broken by repeated calls, is a good strategy. We also note, however, that organisations utilising on-call working time arrangements need to systematically manage the likelihood that on-call sleep can be associated with temporary performance impairments upon waking. Given that the majority of work in this area has been laboratory-based, there is a significant need for field-based investigations of the magnitude of sleep inertia, in addition to the utility of sleep inertia countermeasures. Field studies should include working with subject matter experts to identify the real-world impacts of changes in performance associated with sleeping, or not sleeping, whilst on call.